2023
DOI: 10.1038/s41591-023-02704-x
|View full text |Cite|
|
Sign up to set email alerts
|

First-line talazoparib with enzalutamide in HRR-deficient metastatic castration-resistant prostate cancer: the phase 3 TALAPRO-2 trial

Karim Fizazi,
Arun A. Azad,
Nobuaki Matsubara
et al.

Abstract: Preclinical evidence has suggested an interplay between the androgen receptor, which largely drives the growth of prostate cancer cells, and poly(ADP-ribose) polymerase. This association provides a rationale for their co-inhibition for the treatment of metastatic castration-resistant prostate cancer (mCRPC), an area of unmet medical need. The phase 3 TALAPRO-2 study investigated combining the poly(ADP-ribose) polymerase inhibitor talazoparib with enzalutamide versus enzalutamide alone as first-line treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…At the same time, recent studies propose that the effectiveness of PARPi is not solely dependent on BRCA deficiency but may also be affected by mutations in other genes within HRR pathway ( Boussios et al, 2020 ). In a clinical trial of prostate cancer focusing on alterations in the HRR genes, including BRCA1 , BRCA2 , PALB2 , ATM , ATR , CHEK2 , FANCA , RAD51C , NBN , MLH1 , MRE11A , and CDK12 , the group treated with talazoparib showed a significant improvement in progression-free survival compared to the placebo group ( Fizazi et al, 2023 ). Soon afterwards, the FDA granted further approval for the application of talazoparib in the treatment of prostate cancer patients exhibiting mutations in HRR pathway genes, encompassing CDK12 and RAD51C ( Akbıyık and Ürün, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, recent studies propose that the effectiveness of PARPi is not solely dependent on BRCA deficiency but may also be affected by mutations in other genes within HRR pathway ( Boussios et al, 2020 ). In a clinical trial of prostate cancer focusing on alterations in the HRR genes, including BRCA1 , BRCA2 , PALB2 , ATM , ATR , CHEK2 , FANCA , RAD51C , NBN , MLH1 , MRE11A , and CDK12 , the group treated with talazoparib showed a significant improvement in progression-free survival compared to the placebo group ( Fizazi et al, 2023 ). Soon afterwards, the FDA granted further approval for the application of talazoparib in the treatment of prostate cancer patients exhibiting mutations in HRR pathway genes, encompassing CDK12 and RAD51C ( Akbıyık and Ürün, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most common HRR mutation found in these patients was BRCA2 (34%), followed by ATM (22%), CDK12 (19%), and CHEK2 (18%). Germline mutation testing was positive in 91 out of 302 evaluable patients (30.1%) enrolled in the study [26]. Recent data showed that rPFS was significantly longer in patients with HRRm treated with talazoparib plus enzalutamide compared to those receiving placebo plus enzalutamide (median not reached vs. 13.8 months, HR 0.45, 95% CI 0.33-0.61, p < 0.0001).…”
Section: Talapro-2mentioning
confidence: 95%
“…The rPFS improvement reached 80% in patients with BRCA1/2 alterations (HR 0.20, 95% CI 0.11-0.36, p < 0.0001). Although OS data remain immature, analysis at data cutoff favored the talazoparib group (HR 0.69, 95% CI 0.46-1.03, p = 0.07) [26].…”
Section: Talapro-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Discontinuation rates did not change significantly between the two groups; however, the median time to QoL deterioration was significantly higher in the combined treatment group compared to the PBO plus Enzalutamide group (38.0 versus 25.0 months, HR, 0.78; 95% CI, 0.62 to −0.99; p = 0.04). 67 , 68 …”
Section: Interaction Parpi Of Arsi: Pharmaceutical Induction Of ‘Brca...mentioning
confidence: 99%